2022
DOI: 10.3390/agriculture12122078
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Effect of Sugarcane Stalk Lifting Height on the Cutting Breakage Mechanism Based on the Sugarcane Lifting–Cutting System (SLS)

Abstract: The sugarcane lifting–cutting System (SLS) is the core component of the sugarcane harvester, and the influence of its stalk lifting height on the mechanism of perennial root-cutting damage is still unclear. The test was conducted with the vertical height of centroid (VHC), forward velocity, and cutter rotational speed. Numerical quantification of perennial root based on the cutting breakage effect and cutting breakage grade (CBG) classification was used as the evaluation index. The test results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In area 3, there was the point with the greatest significant distance between the systems (0.41) and the highest damage index observed for the knives during the test (0.67), showing that the knives had difficulty cutting in the double alternating spacing, indicating a greater difficulty in aligning the knives and the crop line. Wang et al [7] showed that Momin et al [27] stated that the choice of inefficient and low-quality cutting systems could compromise the sugarcane field's longevity and reduce the crop's potential. Inadequate cuts cause fractures in the stumps remaining in the soil, preventing future sprouting; therefore, cutting with knives becomes risky in high-productivity sugarcane systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In area 3, there was the point with the greatest significant distance between the systems (0.41) and the highest damage index observed for the knives during the test (0.67), showing that the knives had difficulty cutting in the double alternating spacing, indicating a greater difficulty in aligning the knives and the crop line. Wang et al [7] showed that Momin et al [27] stated that the choice of inefficient and low-quality cutting systems could compromise the sugarcane field's longevity and reduce the crop's potential. Inadequate cuts cause fractures in the stumps remaining in the soil, preventing future sprouting; therefore, cutting with knives becomes risky in high-productivity sugarcane systems.…”
Section: Resultsmentioning
confidence: 99%
“…In area 3, there was the point with the greatest significant distance between the systems (0.41) and the highest damage index observed for the knives during the test (0.67), showing that the knives had difficulty cutting in the double alternating spacing, indicating a greater difficulty in aligning the knives and the crop line. Wang et al [7] showed that some machine devices might be responsible for increased crop losses. Thus, the angle of the cane and the lifting mechanism are fundamental in the shock rates of stumps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…está presente em 121 países, ocupando uma área aproximada de 24 milhões de hectares, e é responsável pelo fornecimento de coprodutos como o açúcar, o etanol e a bioeletricidade. É caracterizada por ser uma cultura semi perene adaptada para as áreas tropicais e subtropicais, cuja importância econômica a torna fundamental para a economia das localidades em que é cultivada [15][16] [17][18] [19].…”
Section: A Monocultura Da Cana-de-açúcarunclassified